1981
DOI: 10.1246/bcsj.54.1392
|View full text |Cite
|
Sign up to set email alerts
|

Structural Interpretation of Plasma-polymerized Tetrafluoroethylene

Abstract: Structural interpretation of plasma-polymerized tetrafluoroethylene produced in a glow discharge chamber is given by referring to 19F-NMR and IR spectroscopy, elemental analysis, and number-average molecular weight determination. The polymer is hardly soluble in the usual organic solvents because of its highly branched structure, making NMR spectroscopy and molecular weight determination impossible. However, the polymer is soluble in 1,2-dibromo-1,1,2,2-tetrafluoroethane and the following structural interpreta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…19 In such a large molecule detected in the GPC measurement, the radical site can be ignored for determining molecular weight distribution of the polymerized fluorocarbon molecule. 20 The prepared sample in the THF solution was injected into the GPC column after a filtration process to remove insoluble substances. The column separated the composites of the sample into several groups depending on their molecular sizes.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…19 In such a large molecule detected in the GPC measurement, the radical site can be ignored for determining molecular weight distribution of the polymerized fluorocarbon molecule. 20 The prepared sample in the THF solution was injected into the GPC column after a filtration process to remove insoluble substances. The column separated the composites of the sample into several groups depending on their molecular sizes.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Considerable literature exists on the infrared (IR) or X-ray photoelectron spectroscopic (XPS) characterization of the products obtained from plasma polymerization of tetrafluoroethylene (TFE), and a somewhat smaller body of literature exists on the IR or XPS characterization of the fluoropolymer deposits formed in the rf plasma sputtering of poly(tetrafluoroethylene) (PTFE). ,, Several references have noted that the structures of the fluoropolymer deposits arising from rf-sputtered PTFE (SPTFE) were similar to those of plasma-polymerized TFE (PPTFE). ,, In none of these earlier studies were SPTFE and PPTFE prepared in the same plasma reactor. Tibbitt et al, who apparently first reported the remarkable similarity of the IR spectra of PPTFE and SPTFE, suggested that the mechanism of rf sputtering of PTFE resembled that of plasma polymerization of TFE.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable literature exists on the infrared (IR) or X-ray photoelectron spectroscopic (XPS) characterization of the products obtained from plasma polymerization of tetrafluoroethylene (TFE), [1][2][3][4][5][6][7][8][9][10][11][12] and a somewhat smaller body of literature exists on the IR or XPS characterization of the fluoropolymer deposits formed in the rf plasma sputtering of poly(tetrafluoroethylene) (PTFE). 9,10,[13][14][15][16][17][18][19][20][21] Several references have noted that the structures of the fluoropolymer deposits arising from rf-sputtered PTFE (SPTFE) were similar to those of plasma-polymerized TFE (PPTFE).…”
Section: Introductionmentioning
confidence: 99%
“…Hewes et al used 19 F and 13 C MAS NMR spectroscopy to follow the direct fluorination of ion exchange resins. Plasma-polymerized tetrafluoroethylene (PPTFE) was shown to consist of a highly branched cross-linked network using 19 F NMR . The high-resolution 19 F magnetic resonance of solids has been reviewed by Harris and Jackson …”
Section: Introductionmentioning
confidence: 99%